Concomitant autoimmune hemolytic anemia and pulmonary embolism associated with mild COVID‐19: A case report - Abdulrahman F. Al‐Mashdali (14777761) (2023)
Despite its rarity, AIHA can be associated with COVID-19. It should be suspected in a patient with recent COVID-19 presenting with unexplained anemia. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/ccr3.4952